Certify and shift blame, or resolve issues? Environmentally and socially responsible global trade and production of timber and tree crops - Mithöfer, D; Noordwijk, M. van; Leimona, B.; Cerutti, P.O. (Informa UK Limited, 2017)
Certification of adherence to social and environmental standards allows companies involved in the (global) trade of commodities to dissociate themselves from negative impacts in the public eye. It can go beyond compliance with legal requirements. Certification can be an attempt to shift blame to uncertified others, but it can also contribute to resolving the underlying issues of concern. We provide a framework for a study of when, where and how certification schemes emerge and evolve, with specific attention to the degree to which underlying issues get addressed. Three strands of literature are combined in this framework (1) the issue–attention cycle as a schematic representation of public concerns shaping policy responses; (2) the management swing potential defined as the gap between best and worst current production systems and the basis for defining standards and (3) global value chains that link distant producers and consumers, and the power relations along these chains, including standards and certification. Based on literature review, we introduce a set of four propositions that inform testable specific hypotheses. We outline questions for reviews, in subsequent papers of this issue, of the experience on timber, oil palm, coffee, cacao and rubber as tropical-forest-margin commodities dominated by global trade.EDITED BY Christian Albert